2016
DOI: 10.1016/j.neulet.2016.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and molecular consequences of Unilateral Naris Closure on two populations of olfactory sensory neurons expressing defined odorant receptors

Abstract: Mammalian olfactory sensory neurons (OSNs), the primary elements of the olfactory system, are located in the olfactory epithelium lining the nasal cavity. Exposed to the environment, their lifespan is short. Consequently, OSNs are regularly regenerated and several reports show that activity strongly modulates their development and regeneration: the peripheral olfactory system can adjust to the amount of stimulus through compensatory mechanisms. Unilateral naris occlusion (UNO) was frequently used to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Additionally, in mosaic analysis, gain of function of the guidance molecules generates duplicated glomeruli, indicating that they can determine the segregation and location of the OSN axons. Later experiments demonstrated that nasal occlusion decreased Kirrel2 expression and increased Kirrel3 expression (Fischl et al, 2014; Molinas et al, 2016; Nakashima et al, 2013). The cell adhesion molecule BIG‐2 (CNTN4) is also identified as an activity‐regulated guidance molecule, which is essential for proper targeting of OSN axons (Kaneko‐Goto et al, 2008) (Figure 1b).…”
Section: Neural Activity and The Establishment And Maintenance Of The...mentioning
confidence: 99%
“…Additionally, in mosaic analysis, gain of function of the guidance molecules generates duplicated glomeruli, indicating that they can determine the segregation and location of the OSN axons. Later experiments demonstrated that nasal occlusion decreased Kirrel2 expression and increased Kirrel3 expression (Fischl et al, 2014; Molinas et al, 2016; Nakashima et al, 2013). The cell adhesion molecule BIG‐2 (CNTN4) is also identified as an activity‐regulated guidance molecule, which is essential for proper targeting of OSN axons (Kaneko‐Goto et al, 2008) (Figure 1b).…”
Section: Neural Activity and The Establishment And Maintenance Of The...mentioning
confidence: 99%
“…While OSN axons initially coalesce to form supernumerary glomeruli during early development, with some of these glomeruli being heterogeneous, over time these connections refine to produce approximately two homogeneous glomeruli per odorant receptor (Potter et al, 2001; Royal & Key, 1999; Strotmann & Breer, 2006). Unilateral naris occlusion has been shown to delay the refinement of both the number and heterogeneity of glomeruli, highlighting the importance of evoked activity (Cummings & Brunjes, 1994; Farbman et al, 1988; Molinas et al, 2016). Activity also plays a key role in the survival of adult‐born OB interneurons (Mandairon et al, 2006).…”
Section: Epoch 3—molding Neuronal Connectivity By Activity and Experi...mentioning
confidence: 99%
“…These observations led the investigators to infer that the open‐side and non‐occluded samples had similar transcript profiles (Coppola & Waggener, 2012). Likewise, comparisons between the open‐side OEs from mice that were UNO‐treated via cautery or plug insertion and the OEs of non‐occluded mice have revealed only subtle differences in OSN electrical activity levels (Barber & Coppola, 2015), OSN axon refinement rates (Zou et al, 2004), OSN synaptic remodeling rates (Cheetham et al, 2016), representations of specific OSN subtypes (Molinas et al, 2016; van der Linden et al, 2020), neurogenesis rates of specific subtypes (van der Linden et al, 2020), and levels olfactory marker protein (Waguespack et al, 2005), which has been found to play roles in OSN signal transduction and axon segregation (Albeanu et al, 2018; Buiakova et al, 1996; Lee et al, 2011). On the other hand, prolonged (6 weeks or more) naris occlusion of adult mice that were UNO‐treated via a combination of cautery and suture was found to cause a reduction in OSN quantities within the rostral region of the open side of the OE (Maruniak et al, 1989).…”
Section: Evidence That Olfactory Deprivation Selectively Reduces the ...mentioning
confidence: 99%